(untitled) (Journal of Partial Differential Equations, 2003)
" We prove that the C00ba boundedness of solution implies the global existence and uniqueness of C00b9 solution to the initial-boundary value problem for linearly degenerate quasilinear hyperbolic systems of diagonal form with nonlinear boundary conditions. Thus, if the C00b9 solution to the initial-boundary value problem blows up in a finite time, then the solution itself must tend to the infinity at the starting point of singularity."